SOSIALISASI PERATURAN MENTERI PENDIDIKAN, KEBUDAYAAN, RISET, DAN TEKNOLOGI REPUBLIK INDONESIA NOMOR 19 TAHUN 2024 TENTANG PENDIDIKAN PROFESI GURU - Sari, Nurullita; Rustandi, Roni; Prastini, Endang (Jurnal Dialektika Politik, 2025)
The current teacher professional education program faces several challenges affecting its effectiveness, including issues in teacher learning, instructor issues, implementation problems, sensemaking issues, and the suboptimal number of pre-service PPG graduates. This community service activity targets teachers and alumni of D4 and S1 education and non-education fields across universities. The method used in this activity is socialization. Activity evaluation is conducted post-socialization by filling out instruments and/or Q&A sessions prepared by the PkM Team regarding participant responses to the activities carried out by the PkM Team of lecturers and students. It is expected that through this PkM activity, the understanding of teachers and alumni of D4 and S1 education and non-education fields across universities regarding the importance of understanding and implementing the Regulation of the Minister of Education, Culture, Research, and Technology of the Republic of Indonesia Number 19 of 2024 on Teacher Professional Education will increase. This will help them face the existing challenges and enhance the overall quality of education.